2010
DOI: 10.1111/j.1600-0501.2010.02045.x
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary sinus vascular anatomy and its relation to sinus lift surgery

Abstract: A sound knowledge of the maxillary sinus vascular anatomy and its careful analysis by CT scan is essential to prevent complications during surgical interventions involving this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(145 citation statements)
references
References 12 publications
(23 reference statements)
9
131
3
2
Order By: Relevance
“…In 2009, Rysz et al [17] studied the anastomosis on foetus cadavers, and clearly the results of the prevalence and distributions were different from the ones reported in the previous studies. Rosano et al [14,15] in 2009-2010 in cadaveric study confirmed the data reported by Solar et al [18] and Traxler et al [18] in 1999. Ilgüy et al [11] in 2013 reported measures, septa presence and that the undetection of the anastomosis on cone beam CT (CBCT) is probably caused by the small diameter.…”
Section: Introductionsupporting
confidence: 81%
“…In 2009, Rysz et al [17] studied the anastomosis on foetus cadavers, and clearly the results of the prevalence and distributions were different from the ones reported in the previous studies. Rosano et al [14,15] in 2009-2010 in cadaveric study confirmed the data reported by Solar et al [18] and Traxler et al [18] in 1999. Ilgüy et al [11] in 2013 reported measures, septa presence and that the undetection of the anastomosis on cone beam CT (CBCT) is probably caused by the small diameter.…”
Section: Introductionsupporting
confidence: 81%
“…Les saignements peropératoires dont l'importance est problématique pour la réalisation de l'acte chirurgical sont rares hormis les lésions de l'artère alvéolo-antrale [22]. Une ligature (72) perforaƟon (9) pas de dépose d'implant dépose d'implant Tableau I. Nombre d'implants déposés selon la perforation ou pas de la membrane sinusienne greffée.…”
Section: Discussionunclassified
“…Regarding Bone augmentation site, to present, 3 months passed from day of surgery. We'll be able to evaluate results in three to four months [27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…Piezo-surgery technique prevents perforation of the "Schneiderian Membrane" and cause minimal postoperative complications. this compared with conventional procedure with rotative instruments used to open lateral window [31]. Oscillation frequency used in Piezo-surgery is designed for acting only on mineralized tissue; therefore, the cutting tip becomes inactive when it comes in contact with soft tissue.…”
Section: Discussionmentioning
confidence: 99%